Pengaruh Persepsi Harga, Lokasi, dan Kualitas Layanan Terhadap Kepuasan Pelanggan Hotel Borobudur Jakarta - Laila Husnia Fauziah; Paludi, Salman (Universitas Fajar, 2025)
This study aims to analyze the influence of price perception, location, and service quality on customer satisfaction at Hotel Borobudur Jakarta, both partially and simultaneously. Customer satisfaction is a crucial factor in the sustainability of the hospitality business as it directly affects customer loyalty and recommendations. This research adopts a quantitative approach with purposive sampling as the sampling technique, involving 100 hotel guests as respondents. Data analysis was conducted using multiple linear regression. The results indicate that, partially, price perception, location, and service quality have a positive and significant effect on customer satisfaction. Simultaneously, these three variables contribute strongly to the level of customer satisfaction. These findings suggest that a combination of reasonable pricing, strategic location, and high-quality service plays a vital role in determining customer satisfaction in the hospitality industry.